Barriers to participation in Iran's Integrated Geriatric Care Program: A qualitative study. - Neda Sadat Nazaripanah; Haidar Nadrian; Vali Bahrevar; Elham Lotfalinezhad; Mina Hashemiparast (PLoS ONE)
Background A significant number of older adults still have unfulfilled needs related to healthcare and social services. Policymakers and health administrators can turn this challenge into a golden opportunity through proper planning and policymaking. This study aimed to identify barriers to participation in Iran's "Integrated Geriatric Care Program (IGCP)". Methods A qualitative study with conventional content analysis approach was conducted in Yazd City, Iran, from January to March 2023. A purposive sampling method with maximum variation was used. Nineteen healthcare providers and community-dwelling older adults participated in the study. Data were collected using semi-structured in-depth interviews until data saturation and were concurrently analyzed. Results Nine older persons (3 women and 6 men) with a Mean±SD age of 71.33±5.75 and ten healthcare providers (6 women and 4 men) with a Mean±SD age of 38.2±9.16 participated in the study. Two main categories, with ten sub-categories, emerged from the data analysis. The main categories were "personal challenges of older adults" and "structural defects of Integrated Geriatric Care Program". Conclusion The participation of community-dwelling older adults in the Iranian IGCP is constrained by a combination of personal and structural factors. Our findings seem to be informative for health policymakers and health practitioners who aim to enhance the quality and quantity of healthcare services for older adults in developing communities.